2015
DOI: 10.1001/jama.2015.10529
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Laparoscopic-Assisted Resection vs Open Resection of Stage II or III Rectal Cancer on Pathologic Outcomes

Abstract: IMPORTANCE Evidence about the efficacy of laparoscopic resection of rectal cancer is incomplete, particularly for patients with more advanced-stage disease. OBJECTIVE To determine whether laparoscopic resection is noninferior to open resection, as determined by gross pathologic and histologic evaluation of the resected proctectomy specimen. DESIGN, SETTING, AND PARTICIPANTS A multicenter, balanced, noninferiority, randomized trial enrolled patients between October 2008 and September 2013. The trial was con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

55
744
15
33

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 999 publications
(874 citation statements)
references
References 20 publications
55
744
15
33
Order By: Relevance
“…Our data have some features such as simultaneous LLN dissection or lower rate of radiotherapy, but we surmise that our results would be generalizable to other countries because similar tendencies could be observed even after stratification by these factors (Figure 3). Regarding radial margin involvement rate, an established risk factor of LR,22, 23, 24, 25 the respective results (4% and 6%) were not inferior to the CRM involvement rates from recent RCTs (3%‐22%) although the radial margins as to criterion of 1 mm or 2 mm were not evaluated in the present study 26, 27, 28, 29. However, it should be noted that most hospitals participating in the present study were leading institutes in cancer care in Japan, such as university hospitals and medical centers.…”
Section: Discussioncontrasting
confidence: 66%
“…Our data have some features such as simultaneous LLN dissection or lower rate of radiotherapy, but we surmise that our results would be generalizable to other countries because similar tendencies could be observed even after stratification by these factors (Figure 3). Regarding radial margin involvement rate, an established risk factor of LR,22, 23, 24, 25 the respective results (4% and 6%) were not inferior to the CRM involvement rates from recent RCTs (3%‐22%) although the radial margins as to criterion of 1 mm or 2 mm were not evaluated in the present study 26, 27, 28, 29. However, it should be noted that most hospitals participating in the present study were leading institutes in cancer care in Japan, such as university hospitals and medical centers.…”
Section: Discussioncontrasting
confidence: 66%
“…The conversion rate was only 11.3% which suggested the quality of surgical experience was high. The authors concluded that their findings did not support the use laparoscopic rectal resection [10] .…”
Section: Evidence From Multicentre Randomised Control Trials (Short Tmentioning
confidence: 87%
“…The landmark multicentre RCTs include the early UK-based MRC CLASICC (Conventional vs. Laparoscopic-Assisted Surgery in Colorectal Cancer) trial [27] , the North American COLOR (Colon Cancer Laparoscopic or Open Resection) II trial [18] , the South Korean based COREAN (Comparison of Open Versus Laparoscopic Surgery for mid or low Rectal Cancer After Neoadjuvant Chemoradiotherapy) trial [20] , the Australian based ALaCaRT (Australian Laparoscopic Cancer of the Rectum Trial) trial [17] and the US based ACOSOG Z6051 [10] .…”
Section: Evidence From Multicentre Randomised Control Trials (Short Tmentioning
confidence: 99%
See 2 more Smart Citations